Cervical and Breast Cancer: Community Health Service and Community Mobilization Development - Sutikno, Djoko (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43600077/Cervical-and-Breast-Cancer-Community-Health-Service-and-Community-Mobilization-Development